Air quality analysis through measurement of pb levels in blood using atomic absorption spectrophotometer - Uitumen Erdenezul (Universitas Lampung, 2021)
Air pollution is a problem that needs attention, especially pollution by heavy metals such as lead (Pb). This research was conducted to measure the levels of Pb in the blood of people who do a lot of daily activities on the highway in the Ulaanbaatar region, Mongolia, so that an overview of the level of exposure to Pb in the air is obtained. The study was conducted using an observational method by measuring the blood directly from the participants using an atomic absorption spectrophotometer. The participants involved were 20 people who met the criteria. The results showed that the average level of Pb in the blood of people who had daily activities on the highway was 8.97 ppm. Where the smallest level is 5.12 ppm and the highest level is 12.06 ppm. This value is far above the threshold value determined by WHO, which is 0.05 ppm. Therefore, it can be concluded that the air quality in the Ulaanbaatar area is in the poor category with a high level of Pb exposure.